Poorly Cohesive (Signet Ring Cell) Carcinoma of the Ampulla of Vater. (May 2020) - Tuncel, Deniz; Basturk, Olca; Bradley, Kyle T.; Kim, Grace E.; Xue, Yue; Reid, Michelle D.; Balci, Serdar; Erbarut, Ipek; Adsay, Volkan
In the ampulla of Vater, carcinomas with "diffuse-infiltrative"/"signet ring cell" morphology, designated as "poorly cohesive carcinoma" (PCC) in the WHO classification, are very rare and poorly characterized. Nine cases with a classical PCC morphology constituting >50% of the tumor were identified. Mean age was 64.8 years (vs 64.6 in ampullary carcinomas [ACs]) and 6 were males, 3 females. The mean invasive tumor size was 2.5 cm (vs 1.9 in ACs). Other morphologic patterns displayed included cord-like infiltration (n=2), plasmacytoid cells (n=2), and microglandular component (n=4), including goblet cell adenocarcinoma-like foci. None of the cases were associated with dysplasia. By immunohistochemistry, the carcinomas did not show intestinal differentiation (CDX2 0/9, CK20 1/9, MUC2 3/9), MUC1 was positive in 4/9, MUC5AC was positive in 7/8. E-cadherin loss was noted in 4/9. All cases were advanced stage (6/9-pT3, 3/9-pT4) (vs 43% in ACs). Lymph node metastases were identified in 44% (vs 45% in AC). Six patients (67%) died of disease at a median of 25 months, 3 were alive at 13, 15, and 60 months. Overall median survival was significantly worse than that of intestinal-type ACs (26 vs 122 months, P = .006) and trended toward worse than pancreatobiliary type (26 vs 42 months, P = .1). In conclusion, PCCs constitute 2.45% of all ACs. These present as advanced tumors and express upper-gastrointestinal immunoprofile with frequent MUC5AC labeling, which may be helpful in identifying subtle infiltration in the surface mucosa since MUC5AC is not expressed in the ampullary mucosa. Patients have poor prognosis.